1999
DOI: 10.1088/0953-4075/32/10/303
|View full text |Cite
|
Sign up to set email alerts
|

Excitation of the lowest autoionizingnp5(n+1)s2,2P3/2,1/2states of Na(n= 2), K(n= 3), Rb(n= 4) and Cs(n= 5) by electron impact

Abstract: Relativistic distorted-wave (RDW) calculations are carried out for the electron impact excitation of the lowest autoionizing states np5(n+1)s2, 2P3/2,1/2 in Na(n = 2), K(n = 3), Rb(n = 4) and Cs(n = 5) alkali atoms from the ground np6(n+1)s, 2S1/2 state. Detailed results in the range of near threshold to 1.5 keV incident electron energies are obtained for total cross sections of the magnetic substates of the individual 2P3/2 and 2P1/2 states. Utilizing these, the results are presented for their total cross sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 26 publications
2
14
0
Order By: Relevance
“…The calculation of A K for the Na [22] and K [22] state np 5 (n+1)s 2 2 P 3/2 has shown that A K was approaching zero when the energy of incoming electrons was increasing. The parameter α 2 = -1 for the np 5 (n+1)s 2 2 P 3/2 states [23]. Our calculations show that it is also equal to -1 for the J = 3 / 2 states of 5p-excited 6s 2 , 5d6s and 6s6p configurations.…”
Section: Resultsmentioning
confidence: 61%
“…The calculation of A K for the Na [22] and K [22] state np 5 (n+1)s 2 2 P 3/2 has shown that A K was approaching zero when the energy of incoming electrons was increasing. The parameter α 2 = -1 for the np 5 (n+1)s 2 2 P 3/2 states [23]. Our calculations show that it is also equal to -1 for the J = 3 / 2 states of 5p-excited 6s 2 , 5d6s and 6s6p configurations.…”
Section: Resultsmentioning
confidence: 61%
“…The final excitation cross sections of lines were obtained by comparing and averaging over the energy position and the line intensity of the data from three separate measurements. The relativistic distorted-wave (RDW) cross section for the (5p 5 6s 2 ) 2 P 3/2 level [27] and the intensity ratio of lines observed in the spectrum at an impact energy of 600 eV were used for the normalization of relative experimental cross sections. After accounting for fluctuations of the experimental conditions, the total relative uncertainty was estimated as 25%.…”
Section: Methodsmentioning
confidence: 99%
“…This was performed based on both new calculations and the fact that the intensity ratio for lines 1 and 17 was 2:1. However, the calculations [13,27] show that due to the considerable relativistic effects and strong configurations mixing, the ratio of the (5p 5 6s 2 ) 2 P 3/2 and (5p 5 6s 2 ) 2 P 1/2 cross sections is far from the statistical value of 2:1 and at 400 eV the impact energy exceeds 3:1. But this value satisfies well the intensity ratio 3.6:1 of lines 1 and 18 observed in the experimental spectrum (see figure 1(b)).…”
Section: Assignment Of Linesmentioning
confidence: 96%
See 1 more Smart Citation
“…Moreover, in the case of core excited states of alkali atoms, only one Auger decay channel is possible [23,24], therefore B(αLSJ, J f ) = 1.…”
Section: Methods Of Calculationsmentioning
confidence: 99%